2010
DOI: 10.1108/18347641011068965
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of corporate disclosure: a meta‐analysis

Abstract: Purpose -The purpose of this paper is to investigate the association between disclosure and seven corporate characteristics which are ownership dispersion, analysts following, audit firm size, leverage, corporate size, profitability, and multi-nationality. Design/methodology/approach -The paper applies the meta-analysis technique developed by Hunter et al. in 1982 to a sample of 16 articles published between 1997 and 2006 for the purpose of cumulating and integrating the findings across studies. Findings -The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 38 publications
(81 reference statements)
6
112
2
2
Order By: Relevance
“…Different researchers have measured leverage differently and the variation was apparent (Khlif, & Souissi, 2010). Considering the sample of commercial banks for the study, the ratio of total debt, including the liabilities to depositors by banks, and the total assets was considered appropriate measure of leverage.…”
Section: Leverage (Lev)mentioning
confidence: 99%
“…Different researchers have measured leverage differently and the variation was apparent (Khlif, & Souissi, 2010). Considering the sample of commercial banks for the study, the ratio of total debt, including the liabilities to depositors by banks, and the total assets was considered appropriate measure of leverage.…”
Section: Leverage (Lev)mentioning
confidence: 99%
“…This study employed ROE as the financial performance indicator following previous studies, such as [27,43]. This study made use of ROE as a measure of financial performance since investors are more interested in ROE and its changes, which provide an indication of the firm's efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, management will disclose detailed information as a means of justifying their position and compensation package (Singhvi & Desai 1971). Khlif and Souissi (2010) found that higher performance allows managers to be more convincing to shareholders of their superior managerial abilities. Therefore, by disclosing more information, managers can obtain higher degrees of confidence from investors.…”
Section: Profitabilitymentioning
confidence: 99%